Prevalence of vitamin D deficiency among doctors in a tertiary care centre in north India - Chodhary, Ishfaq; Mala, Tariq Ahmed; Arif, Tasleem (International Journal of Research in Medical Sciences, 2019)
Background: Vitamin D is unique among vitamins as it can be synthesized from the action of ultra-violet radiation (UVR) upon the skin of human beings. This study was done to investigate the prevalence of vitamin D deficiency among health care professionals. Methods: This was institution based study conducted over a period of two years at Govt. Medical College Hospital. The study was conducted on 200 healthy doctors working in different departments of Govt. Medical College and Associated Hospitals, Jammu for a period of two years. Data regarding demographic characteristics, lifestyle assessment, exposure to sunshine on workdays and weekends, type of clothing, use of sunscreen, subjective general health, dietary assessment and use of calcium or vitamin D supplements was collected using a structured questionnaire. Results: Mean value of age of study subjects was 26.18±2.09 years. Results showed that 50% were male and 50% were females. In this study, 65.50% of the study subjects were Hindu and 30% of study subjects were Muslim. Majority of the study subjects had exposure to sunlight for less than 20 minutes and only 10 out of 200 study subjects had exposure to sunlight for more than 30 minutes. In this study, 97% of the study subjects were vitamin D deficient and only 3% were vitamin D sufficient. Among 196 study subjects with vitamin D deficiency, severe deficiency was present in 30.41% (59 out of 194) of study subjects, moderate deficiency was present in 60.82% (118 out of 194) of study subjects and very few study subjects had mild vitamin D deficiency. Conclusions: Vitamin D deficiency is highly prevalent among healthy medical college students. Lack of awareness regarding importance of vitamin D requirement, inadequate exposure to sunlight, changes in lifestyle and food habits contribute to low vitamin D levels in young population.